Wacana Satirisme pada Konten Digital Kanal Youtube - Brillianing Pratiwi (Universitas Negeri Padang, 2023)
The research aimed to analyze the background reality behind the text/speech, discourse as speech, and sociocultural practices that also examine the impact of satirical discourse on digital content. This is the impact of technological developments directly proportional to the use of social media. The ease of getting information influences the reader/audience. The audience is saturated and needs short entertaining videos. This is marked by the emergence of digital content in the form of cartoons that are suitable for venting frustration or the negative impact of phenomena that are rife. One of the selected digital content is Santoon TV. The selection is based on Santoon TV's most critical content discussing current phenomena. The satirist used by content creators is also more polite than others. The phenomenon of the emergence of digital content in the form of cartoons has developed first in America in the TV series The Simpsons. This research uses descriptive qualitative with critical discourse analysis of Norman Fairclough's theory. This method produces an analysis of the background reality behind the text/speech, discourse as utterances, and sociocultural practices.